ARS pesticide properties database. (Knovel, 2010)
This database has been developed to provide water quality modelers and managers a list of the pesticide properties most important for predicting the potentials of pesticides to move into ground and surface waters under a range of weather and soil conditions.
Keywords: Pesticides -- Environmental aspects -- Databases.; Agricultural chemicals -- Environmental aspects -- Databases.; Water -- Pollution -- Databases.; elektronické knihy; electronic books